Is aortic lymphadenectomy indicated in locally advanced cervical cancer after neoadjuvant chemotherapy followed by radical surgery? A retrospective study on 261 women. Issue 10 (October 2016) - Martinelli, F.; Signorelli, M.; Bogani, G.; Ditto, A.; Chiappa, V.; Perotto, S.; Scaffa, C.; Lorusso, D.; Raspagliesi, F.
Abstract: Objectives: The aim of this study was to estimate the rate of aortic lymph nodes (LN) metastases/recurrences among patients affected by locally advanced stage cancer patients (LACC), treated with neoadjuvant chemotherapy (NACT) and radical surgery. Methods: Retrospective evaluation of consecutive 261 patients affected by LACC (stage IB2–IIB), treated with NACT followed by radical surgery at National Cancer Institute, Milan, Italy, between 1990 and 2011. Results: Stage at presentation included stage IB2, IIA and IIB in 100 (38.3%), 50 (19.2%) and 111 (42.5%) patients, respectively. Squamous cell carcinoma accounted for more than 80%, followed by adenocarcinoma or adenosquamous cancers (20%). Overall, 56 women (21.5%) had LN metastases. Four out of 83 women (5%) who underwent both pelvic and aortic LN dissection had aortic LN metastases, and all women had concomitant pelvic and aortic LN metastases. Only one woman out of 178 (0.5%) who underwent pelvic lymphadenectomy only, had an aortic LN recurrence. Overall 2% of women (5/261) had aortic LN metastases/recurrence. Conclusions: Our data suggest that aortic lymphadenectomy at the time of surgery is not routinely indicated in LACC after NACT, but should reserved in case of bulky LN in both pelvic and/or aortic area. The risk of isolated aortic LN relapse is negligible. Further prospective studies are warranted.